Potential Impact of the REDD+ Program on Poverty Reduction in Nghe An Province, Vietnam - Nguyen, D.T.; Ranola, R.F.; Pham Thu Thuy (MDPI, 2017)
The REDD+ program provides a mechanism for providing financial rewards to forest owners and users who contribute to the reduction of carbon emissions from deforestation and forest degradation. This paper determines the potential impact of the REDD+ program on poverty reduction by comparing income and poverty rate between two household groups that were willing to participate in this study, but that will not participate in the REDD+. The results showed that carbon payment from forests is a significant contributor to the increase in household income of poor people. The average income of households participating in the program is VND 20.68 million in contrast to those not participating whose average income is VND 14.72 million. Results showed that the REDD+ program intervention helped reduce the poverty rate in the two communes by 6.40% (from 39.4% to 33%). The paper recommends that the REDD+ program should facilitate the distribution of land titles to provide security of tenure for individual households that are participating in the program. While the program can contribute to poverty reduction, the program payments can increase income inequality and conflicts between those involved and those not involved in the program and legal ownership of the lands. In addition, a comprehensive research study on the impact of the program on forest conservation and poverty reduction is necessary. Stakeholders of the program should recognize and acknowledge the trade-offs between conservation and economic development or poverty reduction. A comprehensive trade-off analysis of program implementation and a business-as-usual option of commodity production is needed, which could reveal the indirect economic, political, and social costs and benefits of the program.